Development of Water Purification Video as Teaching Material for Middle School Chemistry Course - Hafiz, Muhammad Iqbal Abdul; Hairida, Hairida; Mayasari, Eni (Hydrogen: Jurnal Kependidikan Kimia, 2025)
The purpose of this study was to determine the validity of the Development of Water Purification Videos as Teaching Materials for Junior High School Chemistry Courses. The research method used is Research and Development (R & D) using the ADDIE development model . The subjects of this study were Water Purification Videos assessed by material experts, media experts, and language experts. The research tool used was an assessment sheet using a Likert scale . Data collection techniques used were interviews, observations, and validity assessments. The validation of the water purification video was assessed by two material experts, five media experts, and two language experts. The final results of the assessment showed thatThe water purification video is very valid to be used as teaching material for Middle School Chemistry courses.